Relationship between 2d:4d ratio, handgrip strength, and hamstring muscle length in different sports: a study of volleyball, football and basketball branches - Ahmet Kurtoğlu; Rukiye Çiftçi (Physical Education of Students)
Background and Study Aim. The relationship between the 2nd digit (2D) and the 4th digit (4D) provides much preliminary information about the physiological, psychological, and psychomotor characteristics of individuals. Although there are many studies on the 2D:4D ratio, the number of studies investigating the ratio in different sports is limited. Therefore, the purpose of this study is to determine the relationship between the 2D:4D ratio, posterior thigh muscle length, and handgrip strength in different sports.